Smiles count but minutes matter: Responses to classroom exercise breaks - Howie, Erin; Newman-Norlund, R.; Pate, R. (PNG Publications, 2014)
Objectives: To determine the subjective responses of teachers and students to classroom exercise breaks, and how responses varied by duration. Methods: This mixed-methods experimental study included focus groups with teachers (N = 8) and 4th- and 5th-grade students (N = 96). Students participated in 5-, 10-, and 20-minute exercise breaks and 10minutes of sedentary activity. In an additional exploratory analysis, videotapes of each condition were coded and compared for positive affect. Results: Students and teachers discussed multiple benefits, but teachers discussed barriers to implementing regular breaks of 5-minutes or more. Students exhibited higher positive affect during each exercise condition. Conclusions: Classroom exercise breaks are an enjoyable way to increase physical activity, but additional support may be needed to encourage teachers to implement breaks of 5 minutes or longer.